(untitled) (Research, Society and Development, 2021)
Cotton is the world’s leading fiber crop and contains natural coloring impurities which need to be removed by bleaching. The most applied bleaching methodology utilizes chemical oxidants, such as hydrogen peroxide. This method is carried out at high temperatures and under strong alkaline conditions, entailing high-energy consumption, strong alkaline effluents and severe fiber damage. The development of milder and greener bleaching processes, in which the fibers are less damaged, is a goal that has long been pursued. Another approach for cotton bleaching is the use of sodium hypochlorite as an oxidant. Several methods applying hypochlorite are known, but they face problems associated with the transport, storage and handling of unstable and hazardous chemicals. Here we present a mild methodology for in situ electrogeneration of hypochlorite from sodium chloride or potassium chloride, and its application in bleaching of cotton, thus reducing the problems associated with the transport and storage of the oxidizing reagent. Our methodology was able to bleach the cotton fibers with a comparable whiteness degree, when compared to the conventional one, and it is carried out in lower reaction times, at room temperature, with no need of addition of hazardous materials and avoiding the production of residual hypochlorite.